Medication Adherence and Social Support in Regards to Apprehension of Death in People Living with HIV/AIDS - Rachmawati Rachmawati (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2018)
Apprehension of death for People Living with HIV and AIDS (PLWA) is influenced by discipline in their adherence to their medication regimen and the social support they receive. This research aims to study the roles of discipline in adherence to their medication regimen and of social support, in regards to their apprehension of death, for PLWA. The data collection method employed a scale of discipline in adhering to a medication regimen, a scale of the social support received, and a scale of the apprehension of death. The subjects of this research were 89 people with positive HIV/AIDS status, living in South Sumatera. Data analysis was by multiple regression. The multiple regression analysis results indicated that both adherences to a medication regimen, and social support, play roles in regards to apprehension of death. (R2 = 0.113; F = 5.473; p < 0.05). This research affirms the importance of internal and external factors in reducing the level of apprehension of death for PLWA.